PENGARUH MEDIA PEMBELAJARAN PAPAN PINTAR PANCASILA TERHADAP HASIL BELAJAR SISWA UPTD SDN BUDDAN 2 - Azkadin Nada; Ihwan Firmansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Pancasila smart boardmedia on the learning outcomes of class 2 students of UPTD SDNBuddan 2. The approach in this study is a quantitative approach usingthe experimental method and one group pretest-posttest design researchdesign. The population used was class 2 UPTD SDN Buddan 2 totaling30 students. The sample of this study used the entire researchpopulation. The instruments used in this study were questions tomeasure student learning outcomes. The data analysis techniques usedin this study were validity tests, reliability tests, normality tests andpaired sample tests. The results obtained from the paired sample t-testof the activeness questionnaire were known to have a sig. (2-tailed)0.000 < 0.05, and the results of the paired sample t-test of learningoutcome questions were known to have a sig. (2-tailed) 0.000 < 0.05,which means that there is an influence of the Pancasila smart boardmedia on student learning outcomes and there is an influence